A novel nonsense ATP2C1 mutation causes Hailey-Hailey disease in a Tunisian family - Marwa Chourabi; Dorra H'mida-Ben Brahim; Carine Bonnard; Amina Aounallah; Alvin Yu Ng; Sumanty Tohari; Byrappa Venkatesh; Ali Saad; Lobna Boussofara; Bruno Reversade; Mohamed Denguezli (Our Dermatology Online, 2018)
Background: Hailey-Hailey disease (HHD) is an autosomal dominant blistering skin disorder that manifests in the third to fourth decade of life. The ATP2C1 has been identified as the pathogenic gene of this disease since 2000. Materials and Methods: We report here a three generations Tunisian pedigree, where almost all males are severely affected and present with complete penetrance of HHD, while only one female shows a mild disease's phenotype in her fourth decade. A molecular study using Whole exome sequencing and direct sequencing was performed to this family. Results: By whole exome sequencing and direct DNA sequencing, a novel nonsense mutation in ATP2C1 (c.2698A>T; p.Lys900Ter) was identified in all patients, supporting that alterations in ATP2C1 are causative of HHD. Unexpectedly, this mutation was found in one female who was initially not diagnosed for HHD. Our observations would be in line with incomplete penetrance and variable expressivity between male and female of this disease, or evidence for genetic modifiers. Conclusion: We report here a novel nonsense heterozygous mutation in ATP2C1 gene in 5 patients with HHD. Interestingly, one woman carries the nonsense ATP2C1 mutation but displays a mild phenotype of HHD. This could indicate a variation in pattern and expressivity between male and female developing HHD phenotype which should be considered when providing genetic counselling to family members carrying such mutations.